2013
DOI: 10.1017/s0007485312000880
|View full text |Cite
|
Sign up to set email alerts
|

Performance and feeding behaviour of two biotypes of the black currant-lettuce aphid,Nasonovia ribisnigri, on resistant and susceptibleLactuca sativanear-isogenic lines

Abstract: The black currant-lettuce aphid, Nasonovia ribisnigri, is an important pest of cultivated lettuce, Lactuca sativa. Since 1982, the control of this aphid on lettuce is largely based on host plant resistance, conferred by the Nr gene, introgressed from Lactuca virosa. The resistance mechanism remains to be identified. N. ribisnigri populations virulent on the Nr-based resistance in lettuce have emerged in several locations in Europe since 2007. The objective of this study was to investigate the resistance mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 53 publications
4
30
1
Order By: Relevance
“…For details on the EPG methods used, see ten Broeke et al. (). Winged adult aphids (alatae, the colonizing stage of aphids) were randomly collected from the rearing, to obtain a general view on the behaviour of alatae within a population.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For details on the EPG methods used, see ten Broeke et al. (). Winged adult aphids (alatae, the colonizing stage of aphids) were randomly collected from the rearing, to obtain a general view on the behaviour of alatae within a population.…”
Section: Methodsmentioning
confidence: 99%
“…Since 2007, a virulent biotype of N. ribisnigri (Nr:1 biotype) has been reported infesting resistant lettuce, making the Nr ‐resistance ineffective (Thabuis et al., ). An Nr:1 population from Germany performed equally well on resistant and susceptible lettuce and did not seem to be affected by the Nr ‐resistance (ten Broeke et al., ). In a previous study, it was shown that there is large variation in virulence among populations of N. ribisnigri ; however, it remains unclear what caused this variation (ten Broeke et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In the EPG set-up, a plant and a piercing insect are made part of an electrical circuit, by attaching a thin gold wire to the insect's dorsum and inserting an electrode in the soil of the plant. For details on the EPG methods used see Ten Broeke et al (2013). Eight hour recordings were made from winged adult aphids (alatae) of unknown age of N. ribisnigri and M. euphorbiae aphids.…”
Section: Epg Recordingmentioning
confidence: 99%
“…Nr:0 aphids are not able to ingest phloem and cannot survive on resistant lettuce. In contrast, Nr:1 aphids are able to survive and ingest phloem of resistant lettuce, performing equally well on resistant and susceptible lettuce cultivars (Ten Broeke et al 2013). The mechanism underlying the virulence of Nr:1 aphids is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation